Anti-herpesvirus activity of the acyclic nucleoside 9-(1,3-dihydroxy-2-propoxymethyl)guanine. - Smee, D F (1983)
The antiherpetic effects of a novel purine acyclic nucleoside, 9-(1,3-dihydroxy-2-propoxymethyl)guanine (DHPG), were compared with those of acyclovir in cell cultures and in mice. The modes of action of DHPG and acyclovir were similar in that herpes thymidine kinase phosphorylated each compound, and both agents selectively inhibited viral over host cell DNA synthesis. In 50% plaque reduction assays in Vero cells, the drugs inhibited herpes simplex virus types 1 and 2 thymidine kinase-positive strains at 0.2 to 2.4 microM. DHPG was markedly more active than acyclovir against human cytomegalovirus (50% inhibitory doses were 7 and 95 microM, respectively). Each nucleoside inhibited uninfected cell macromolecule synthesis and cell proliferation at concentrations far above those required to inhibit herpes simplex virus replication. Although the two compounds had many similarities in their behavior in vitro, the important difference was the superior performance of DHPG against herpesvirus-induced encephalitis and vaginitis in vivo. Thus, mortality in mice infected with herpesvirus type 2 was reduced 50% by daily doses of 7 to 10 mg of DHPG/kg, whereas an equally effective daily dose of acyclovir was approximately 500 mg/kg. DHPG at a daily dose of 50 mg/kg was also superior to acyclovir at 100 mg/kg per day in its inhibition of herpetic vaginal lesions in mice.